Hubungan Durasi Tidur dengan Kejadian Astenopia pada Mahasiswa Keperawatan Universitas Tanjungpura saat Pandemi Covid-19 - Delia Mentari; Mita Mita; Argitya Righo (Universitas Malahayati Lampung, 2024)
ABSTRACT Asthenopia is eye fatigue because the eye muscles are forced to work hard, especially when they have to see close objects for a long time, one of the causes of asthenopia is lack of sleep or rest. Symptoms of asthenopia divided into three parts: ocular symptoms, visual symptoms and extraocular symptoms. This research aims to identify the correlation between sleep duration with asthenopia incidence. This research is correlational and uses a cross sectional approach. The research sample was obtained using purposive sampling method with a sample of 203 students who were Nursing student of UNTAN consisting of the class 2018, 2019, 2020 and 2021. Data collection used Visual Vatigue Index (FVI) questionnaire. Spearman rho correlation test was used for statistical tests. The results of univariate analysis showed that 47.3% of respondents had insufficient sleep duration (7 hours/day), 50.2% normal sleep duration (7-9 hours/day) and 16.3% excessive sleep duration (9 hours/day). Then 2.5% of respondents did not experience asthenopia and 71.4% of respondents had asthenopia. The results of the bivariate test showed that there was a relationship between sleep duration with asthenopia incidence in Nursing students during COVID-19 pandemic (p=0,009). There is a relationship between the sleep duration with asthenopia incidence in Nursing students during COVID-19 pandemic. Keywords: Sleep Duration, Asthenopia, Nursing Students ABSTRAK Astenopia merupakan kelelahan mata karena otot mata dipaksa bekerja keras terutama saat harus melihat objek dekat dalam waktu yang lama, salah satu penyebab astenopia adalah kurangnya tidur atau istirahat. Gejala astenopia dapat berupa gejala okuler, gejala visual dan gejala ekstraokuler. Penelitian ini bertujuan untuk mengidentifikasi hubungan durasi tidur dengan kejadian astenopia. Penelitian ini menggunakan pendekatan cross sectional dan bersifat korelasional. Sampel diambil dengan menggunakan teknik purposive sampling dengan jumlah responden 203 orang mahasiswa Program Studi Keperawatan UNTAN yang terdiri dari angkatan 2018, 2019, 2020 dan 2021. Pengambilan data menggunakan kuesioner Visual Vatigue Index (FVI). Uji statistik menggunakan uji korelasi Spearman rho. Hasil analisis univariat didapatkan 47,3% responden memiliki durasi tidur kurang (7 jam/hari), 50,2% durasi tidur normal (7-9 jam/hari) dan 16,3% durasi tidur berlebih (9 jam/hari). Kemudian 2,5% responden tidak mengalami astenopia dan 71,4% responden mengalami astenopia. Hasil uji bivariat menunjukkan bahwa terdapat hubungan antara durasi tidur dengan kejadian astenopia pada mahasiswa Program Studi Keperawatan saat pandemi COVID-19 (p=0,009). Terdapat hubungan antara durasi tidur dengan kejadian astenopia pada mahasiswa Program Studi Keperawatan saat pandemi COVID-19. Kata Kunci: Durasi Tidur, Astenopia, Mahasiswa Keperawatan